Requirements to the library collection quality in culturological studies of the Russian library researchers - O. N. Moreva (Библиосфера, 2016)
A cultural approach is widely used in the library science and can be productive for revealing parameters of the library collection quality as a cultural phenomenon. The analysis of scientific publications shows that requirements to the library collection are derived from its culture-saving, classifying, modeling, communicative-educational and culture-creating functions, as well as its protective role in the society. In terms of culture the main task of the total library holdings is true and sufficiently complete reflection of the culture as a whole system, including not only the knowledge, values, the human spirit best achievements, but also the diversity of cultural forms, phenomena, languages of culture in their complicated and heterogeneous relationships. A significant part of the library collection qualitative characteristics is requirements of adequate documents selection to a level of difficulty and novelty with respect to engaging users different groups in the culture semiotic system, comfort, timeliness and forms variety of access to documents from the collection to introduce citizens to cultural achievements.